Effectiveness of seasonal influenza vaccine in Australia, 2015: An epidemiological, antigenic and phylogenetic assessment - Fielding, J.; Levy, A.; Chilver, M.; Deng, Y.; Regan, Annette; Grant, K.; Stocks, N.; Sullivan, S. (Elsevier, 2016)
Background: A record number of laboratory-confirmed influenza cases were notified in Australia in 2015, during which type A(H3) and type B Victoria and Yamagata lineages co-circulated. We estimated effectiveness of the 2015 inactivated seasonal influenza vaccine against specific virus lineages and clades. Methods: Three sentinel general practitioner networks conduct surveillance for laboratory-confirmed influenza amongst patients presenting with influenza-like illness in Australia. Data from the networks were pooled to estimate vaccine effectiveness (VE) for seasonal trivalent influenza vaccine in Australia in 2015 using the case test-negative study design. Results: There were 2443 eligible patients included in the study, of which 857 (35%) were influenza-positive. Thirty-three and 19% of controls and cases respectively were reported as vaccinated. Adjusted VE against all influenza was 54% (95% CI: 42, 63). Antigenic characterisation data suggested good match between vaccine and circulating strains of A(H3); however VE for A(H3) was low at 44% (95% CI: 21, 60). Phylogenetic analysis indicated most circulating viruses were from clade 3C.2a, rather than the clade included in the vaccine (3C.3a). VE point estimates were higher against B/Yamagata lineage influenza (71%; 95% CI: 57, 80) than B/Victoria (42%, 95% CI: 13, 61), and in younger people. Conclusions: Overall seasonal vaccine was protective against influenza infection in Australia in 2015. Higher VE against the B/Yamagata lineage included in the trivalent vaccine suggests that more widespread use of quadrivalent vaccine could have improved overall effectiveness of influenza vaccine. Genetic characterisation suggested lower VE against A(H3) influenza was due to clade mismatch of vaccine and circulating viruses.